Data from: Satellite telemetry reveals higher fishing mortality rates than previously estimated, suggesting overfishing of an apex marine predator - Byrne, Michael E.; Cortés, Enric; Vaudo, Jeremy J.; Harvey, Guy C. McN.; Sampson, Mark; Wetherbee, Bradley M.; Shivji, Mahmood (Dryad Digital Repository, 2020)
Overfishing is a primary cause of population declines for many shark species of conservation concern. However, means of obtaining information on fishery interactions and mortality, necessary for the development of successful conservation strategies, are often fisheries-dependent and of questionable quality for many species of commercially exploited pelagic sharks. We used satellite telemetry as a fisheries-independent tool to document fisheries interactions, and quantify fishing mortality of the highly migratory shortfin mako shark (Isurus oxyrinchus) in the western North Atlantic Ocean. Forty satellite-tagged shortfin mako sharks tracked over 3 years entered the Exclusive Economic Zones of 19 countries and were harvested in fisheries of five countries, with 30% of tagged sharks harvested. Our tagging-derived estimates of instantaneous fishing mortality rates (F = 0.19–0.56) were 10-fold higher than previous estimates from fisheries-dependent data (approx. 0.015–0.024), suggesting data used in stock assessments may considerably underestimate fishing mortality. Additionally, our estimates of F were greater than those associated with maximum sustainable yield, suggesting a state of overfishing. This information has direct application to evaluations of stock status and for effective management of populations, and thus satellite tagging studies have potential to provide more accurate estimates of fishing mortality and survival than traditional fisheries-dependent methodology. Byrne_et_al_data_readmeInformation about contents of data files for tagging, fate, and harvest information.Byrne_et_al_Mako_Tagging_Fate_dataTagging information and ultimate fate of all mako sharks in this study.Can be used to recreate survival analysisByrne_et_al_Harvest_dataInformation on all harvest events